Seed Systems: Resilient, Equitable, and Integrated - Fadda, Carlo; Legg, James; McEwan, Margaret; Aighewi, Beatrice; Andrade, Jorge; Bishaw, Zewdie; Carsan, Sammy; Cole, Steven Michael; Duncan, Alan; Galie, Alessandra; Garrett, Karen; Hellin, Jonathan; et al. (2021)
Lead Authors: Carlo Fadda James Legg Margaret McEwan Beatrice Aighewi Jorge Andrade Zewdie Bishaw Sammy Carsan Steven Michael Cole Alan Duncan Alessandra Galie Karen Garrett Jonathan Hellin James Lillesø Chris Stephen Jones Christopher Kettle Jan Kreuze Kumar, Lava Jens-Peter Barnekow Lillesø Alice Muchugi Bonaventure Aman Omondi Michael Peters Kelvin Mashisia Shikuku David Spielman Ronnie Vernooy